Stereoselective Synthesis of Spirocyclic Oxindoles via Prins Cyclizations - Castaldi, M. Paola (2009)
[Image: see text] The synthesis of spirocyclic oxindole pyran and oxepene frameworks using highly stereoselective Prins cyclizations of homoallylic and bis-homoallylic alcohols and isatin ketals is described.